Newcomer Information Seeking: Exploring Types, Modes, Sources, and Outcomes - Morrison, Elizabeth Wolfe (Academy of Management Journal, 1993)
This study provides insight into the organizational newcomer information-seeking process. Surveys were given to 205 new accountants one, three, and six months into their jobs. Patterns of seeking varied by the type of information being sought. Newcomers sought technical information primarily by asking others and sought other types of information primarily through observation. Further, they sought technical information, information about role demands, and performance feedback mostly from supervisors but sought normative and social information mostly from peers. These patterns were stable over time. Information seeking was also related to satisfaction, performance, and intentions to leave an organization. The results support a view of newcomers as ?proactive.?